2014
DOI: 10.3896/ibra.1.53.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of parasites and pathogens in honey bee colonies used in a European genotype-environment interactions experiment

Abstract: SummaryDiseases are known to be one of the major contributors to colony losses. Within a Europe-wide experiment on genotype -environment interactions, an initial 621 colonies were set up and maintained from 2009 to 2012. The colonies were monitored to investigate the occurrence and levels of key pathogens. These included the mite Varroa destructor (mites per 10 g bees), Nosema spp. (spore loads and species determination), and viruses (presence/absence of acute bee paralysis virus (ABPV) and deformed wing virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 83 publications
6
69
0
3
Order By: Relevance
“…Consequently, professional beekeepers are looking for alternatives to treat their colonies and improve the overall colony health status. Nosema infection levels are naturally lower in the summer compared to spring and autumn (Meixner et al, 2014), which has also been demonstrated in this study, probably due to the more rapid replacement of the older bees with emerging bees. It is also a common beekeeping practice to feed colonies in spring with sugar syrup for stimulation, which further facilitates population replacement and naturally reduces nosema spore loads.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Consequently, professional beekeepers are looking for alternatives to treat their colonies and improve the overall colony health status. Nosema infection levels are naturally lower in the summer compared to spring and autumn (Meixner et al, 2014), which has also been demonstrated in this study, probably due to the more rapid replacement of the older bees with emerging bees. It is also a common beekeeping practice to feed colonies in spring with sugar syrup for stimulation, which further facilitates population replacement and naturally reduces nosema spore loads.…”
Section: Resultssupporting
confidence: 55%
“…All colonies were naturally infected with N. ceranae as previously demonstrated in other studies (Hatjina et al, 2010(Hatjina et al, , 2011Meixner et al, 2014) and were maintained at the apiary site of the Division of Apiculture, Institute of Animal Science, Chalkidiki, Greece for the duration of the experiment. At the start of the study in November 2012, all colonies were equalized to ensure each colony had approximately six frames of bees and sister queens.…”
Section: Experimental Designmentioning
confidence: 99%
“…Meixner et al (2015) reviewed some studies concerning Varroa -resistant populations of EHBs. Their compilation highlights that colonies descending from a specific survivor population, when tested outside their native environment, often succumb to Varroa infestation, reinforcing the conception that resistance traits are strongly influenced by genotype-environment interactions (Costa et al 2012;Büchler et al 2014;Meixner et al 2014Meixner et al , 2015. It is plausible to suppose that the European bees on Fernando de Noronha are now only able to survive Varroahaplotype J infestation under the tropical weather conditions found on the island.…”
Section: Discussionmentioning
confidence: 91%
“…This species is less resistant to low temperatures than N. apis (Fenoy et al, 2009;Fries, 2010;Gisder et al, 2010;Chen et al, 2012). Considering this fact, we expected the distribution of N. ceranae in our climate to be similar to those levels identified for cooler regions Forsgren and Fries, 2013;Meixner et al, 2014). It turned out, though, that the prevalence of N. ceranae in Poland is more similar to SouthEuropean areas, with a simultaneous relatively high incidence of N. apis.…”
Section: Epidemiological Situationmentioning
confidence: 79%
“…The results of COLOSS GenotypeEnvironment Interactions experiment has also proved the existence of significant interactions between honey bee genotypes and the environment which affect the survival of Apis mellifera L. colonies in Europe Meixner et al, 2014). Due to the genetic variability of honey bee populations and the wide variety of honey bee breeding conditions it is impossible to indicate the global causes for the mass dying out of bee colonies.…”
Section: Honey Bee Colony Lossesmentioning
confidence: 99%